Is intravenous fish oil associated with the neurodevelopment of extremely low birth weight preterm infants on parenteral nutrition?. Issue 5 (May 2021) - Biagetti, Chiara; Correani, Alessio; D'Ascenzo, Rita; Ferretti, Enrica; Proietti, Cecilia; Antognoli, Luca; Giretti, Ilaria; Pompilio, Adriana; Cogo, Paola; Carnielli, Virgilio P.
Summary: Background & aims: Preterm infants are at increased risk of long-term neurodevelopmental disabilities (NDD). Long chain n-3 fatty acids play a key role during the development of the central nervous system and some studies in preterm infants showed benefits of docosahexaenoic acid and arachidonic acid supplementation for visual and cognitive development. In recent years fish oil has been added to the fat blend of intravenous (IV) lipid emulsions (LE) but to date scanty data are available on neurodevelopmental outcome of preterm infants that received fish oil containing LE. We studied the effect of fish oil containing IV LE vs standard IV LE on neurodevelopment in a large cohort of preterm infants who received routine parenteral nutrition (PN) from birth. Methods: We retrospectively reviewed the neurodevelopmental outcome of 477 preterm infants (birth weight (BW): 400–1249 g and gestational age (GA) at birth: 24 +0 - 35 +6 weeks (W)) admitted to our NICU between Oct-2008 and June-2017, who received routine PN with different LE, with and without fish oil (IV-FO vs CNTR). We compared neurodevelopment at 2 years corrected age by the Bayley III development scale and the incidence of NDD. Results: Demographics, birth data and the incidence of the main clinical short-term outcomes of prematurity were similar in the two groups (IV-FO: n = 178, GA 197 ± 14 days, BW 931 ± 182 g; CNTR: n = 192, GA 198 ± 15 days, BW 944 ± 194 g). No differences were found in maternal demographics nor in parental education between the two groups. Cognitive score was not significantly different between IV-FO and CNTR (92 ± 15 vs 93 ± 13, p = 0.5). No differences were found in motor and language scores, and in the incidence of NDD in the two groups. Conclusions: Contrary to our hypothesis, the use of fish oil containing LE in a large cohort of preterm infants on routine PN did not result in better neurodevelopment. Large randomized controlled trials powered for neurodevelopment are needed to clarify the impact of the widely used fish oil containing LE on neurodevelopment of preterm infants.